Electronic Business Development Efforts Based on Local Ceremony in Pringsewu District - Ferry Susanto (Journal of Intelligent Business and Technology Science (JIBTec), 2022)
Electronic business is an example of an internet technology-based strategy that can help businesses to communicate and distribute goods and services to consumers. today's business competition is very tight and a variety of product innovations. to reach the desired market and win the business competition that can provide adequate profits entrepreneurs need to know what factors can influence the success of a business. the purpose of this study mapping the characteristics of local wisdom entrepreneurs in Pringsewu Regency, knowing the factors that most influence business success in the Pringsewu district. the analytical method used in this study is descriptive analysis and true logistic regression. factors that influence the success of the banana chips business are product price, business name, and initial capital of the business.